The study of relationship between phosphorus and glyphosate on macronutrient availability in mineral soil / Mohd Farhin Ahmad - Ahmad, Mohd Farhin (Faculty of Plantation and Agrotechnology, 2016)
A two month study evaluating the relationship between phosphorus and glyphosate on the macronutrients availability in mineral soil had been carried out. This experiment was carried out in the green house at UiTM Malacca, Jasin campus.Three parameters were observed that are K, Ca and Mg availability in mineral soil. The use of phosphorus and glyphosate is essential in improving soil productivity and crop production. CIRP (Christmas Island Rock Phosphate) of 0.9 g, 1.8 g, 3.6 g and 7.2 g was mixed with 2 kg soil treated with 7 ml of glyphosate for each treatment. Shaking method was used to determine the potassium, calcium and magnesium availability. The samples were watered everyday so that phosphorus and glyphosate would react with the macronutrients in the soil. Samples were collected at two week intervals for analysis. The Completely Randomized Design (CRD) was used with five treatments and four replications. A significant increase in potassium, calcium and magnesium availability in soil were observed for all treatments involving phosphorus and glyphosate. The higher rate of phosphorus (7.2) resulted in high K, Ca and Mg available in soil.